2016
DOI: 10.3382/ps/pew140
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of dietary supplementation with mannan oligosaccharide and oregano essential oil in forced molted and fully fed laying hens between 82 and 106 weeks of age

Abstract: The aim of this study was to investigate the efficacy of feed-grade preparations of mannan oligosaccharides ( MOS: ) and oregano essential oil ( OEO: ) in forced molted or fully fed 82-week-old, laying hens. A 2 × 3 factorial experiment investigated the influence of molting vs. full feeding and dietary supplements [i.e., unsupplemented control, MOS (1 g/kg) diet, and OEO (24 mg/kg) diet] on production parameters, egg quality, serum stress indicators, blood constituents, tibial characteristics, liver antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 62 publications
2
23
2
2
Order By: Relevance
“…The result reflected that mg/kg EOs improved the bio-availability of Ca in laying hens. Similarly, it was determined that 400 and mg/kg oregano EOs [17] and mg/kg rosemary or cinnamon [34] increased serum Ca concentration, whereas 0.5 and 1.0 mg/kg bergamot oil decreased it [35], but 250 mg/kg thymol [11] and 24 mg/kg oregano EOs [12] did not change serum Ca concentration in laying hens. It was reported that EOs could positively affect serum Ca and P concentration probably by improving intestinal morphology and oxidative stress or by increasing intestinal pH [40].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…The result reflected that mg/kg EOs improved the bio-availability of Ca in laying hens. Similarly, it was determined that 400 and mg/kg oregano EOs [17] and mg/kg rosemary or cinnamon [34] increased serum Ca concentration, whereas 0.5 and 1.0 mg/kg bergamot oil decreased it [35], but 250 mg/kg thymol [11] and 24 mg/kg oregano EOs [12] did not change serum Ca concentration in laying hens. It was reported that EOs could positively affect serum Ca and P concentration probably by improving intestinal morphology and oxidative stress or by increasing intestinal pH [40].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Functional oligosaccharides are widely used in animal feed because of the benefits to animal growth and immunity (Duan et al, 2016). Mannanoligosaccharide (MOS) has been identified as a typical functional oligosaccharide (Patel and Goyal, 2011) and has been the subject of several studies on animals including pigs (Giannenas et al, 2016;Valpotic et al, 2016), laying hens (Bozkurt et al, 2016;Ghasemian and Jahanian, 2016), broiler chickens (Attia et al, 2014), rabbits (Abdel-Hamid and Farahat, 2016), and aquaculture (Akter et al, 2016;Torrecillas et al, 2016). Most previous studies concentrated on monogastric animals, because it is believed that oligosaccharides are degraded by ruminal microbes and therefore bring no additional benefit to ruminant diets.…”
Section: Introductionmentioning
confidence: 99%
“…Then, during the first 15 D of the experimental trial period, the hens in the CON group were fed ad libitum on a regular layer hen diet and not subjected to molting with normal illumination (16L: 8D). At the same time, the hens of TFE1 and TFE0 groups were fasted and light shaded by a dark nylon cover that allowed no light transfer to isolate molted hens from that of the unmolted hens ( Bozkurt et al., 2016 ). The molted period was 15 D; hens of 3 groups drank water ad libitum throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The hens go into reduction states resulting in various hormone secretions, which ultimately lead to follicular and reproductive system organ atrophy ( Gongruttananun et al., 2017 , Socha et al., 2017 ). Significant regression in ovary and oviduct weights ( P < 0.01) has been observed in molting hens ( Bozkurt et al., 2016 ). It was found that the oviduct weights and lengths of the late-phase molting layer hens not fully fed with cassava meal for 3 or 4 wk were diminished in comparison with the control group ( Gongruttananun et al., 2017 ).…”
Section: Introductionmentioning
confidence: 93%